2018
DOI: 10.20402/ajbc.2018.0203
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Anti-oxidative and Whitening Effects of Complex Extracts Obtained from Sprout Panax ginseng C.A. Meyer and Cassia nomame (Sieb.) Honda on Skin

Abstract: Purpose: In this study, we tried to develop differentiated natural cosmetic materials through the standardization of optimal raw materials, and demonstrate complex functionality with anti-oxidative and whitening effects of natural extracts of sprout Panax ginseng C.A. Meyer and Cassia nomame (Sieb.) Honda. Methods: In this experiment, the research materials, sprout Panax ginseng C.A. Meyer and Cassia nomame (Sieb.) Honda, were prepared by identification of genetic analysis, complex extracts of sprout Panax gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…이때 납, 비소 표준용액의 농도는 0.1, 0.5 및 Ⅲ. 항염증 항염증 확인을 위한 Raw 264.7 세포(Korea cell line bank, KCLB; Korea)는 90% DMEM에 10% FBS 및 1% P/S를 첨가하 고, incubator에서 37℃, 5% CO 2 조건으로 배양하였다 (Kim et al, 2018;Shim, 2019;Kim & Ko, 2020) We confirmed the Dendropanax extracts' concentration to 0.1 mg/mL (A) because of the cytotoxicity at higher concentrations, whereas the concentration was established as 5 mg/mL for sea salt (B), spinach (C), and kelp (D). Each bar indicates the mean± standard deviation of determinations (n=3).…”
Section: ⅰ 중금속mentioning
confidence: 99%
“…이때 납, 비소 표준용액의 농도는 0.1, 0.5 및 Ⅲ. 항염증 항염증 확인을 위한 Raw 264.7 세포(Korea cell line bank, KCLB; Korea)는 90% DMEM에 10% FBS 및 1% P/S를 첨가하 고, incubator에서 37℃, 5% CO 2 조건으로 배양하였다 (Kim et al, 2018;Shim, 2019;Kim & Ko, 2020) We confirmed the Dendropanax extracts' concentration to 0.1 mg/mL (A) because of the cytotoxicity at higher concentrations, whereas the concentration was established as 5 mg/mL for sea salt (B), spinach (C), and kelp (D). Each bar indicates the mean± standard deviation of determinations (n=3).…”
Section: ⅰ 중금속mentioning
confidence: 99%
“…이러한 시장 변화는 화장품 업계도 예외가 아니어 서 자연과 건강을 접목시킨 친환경 활동의 화장품 브랜드 이미지가 강조되고 있다 (Kim et al, 2016a). 화장품 기업에서의 친환경 활동이란 자연에서 가져온 원료를 사용하거나 (Jeong & Yoo, 2018), 가공과정을 최소화 (Kim et al, 2018)하고, 포장 및 유통, 재순환을 통해 자연의 일부인 인간이 자연과 함께 공생하고 자연을 보호하면 서 소비활동을 하는 일련의 과정을 의미한다 (Kim et al, 2018…”
Section: 연구의 필요성 및 목적unclassified
“…최근 화장품 유해성분에 대한 위험성 문제와 친환경적인 제품 을 선호하는 소비자로 인해 천연 화장품 시장이 세계적으로 증가하 고 있다. 국내에서도 천연화장품 개발이 꾸준히 증가 추세에 있으며 국내산 천연화장품 소재의 효능 (Kim et al, 2018;Hwang et al, 2020)이 검증되어 다양한 제품으로 출시되고 있다. 특히 해외에서 한국 화장품의 구매가 증가하면서 해외 소비자에게 인지도가 높은 국내산 천연물을 소재로 한 화장품 연구도 활발히 진행되고 있다.…”
Section: Introductionunclassified